6)
34, 43, 52, 61, ...
43-34 = 9; 52-43 = 9; 61-52 = 9
The difference between one term and the next is a constant so it is arithmetic sequence
first term: a = 34
difference: d = 9
so the formula:
7)
10, 6, 2, -2, ...
6-10 = -4; 2-6 = -4; -2-2 = -4
The difference between one term and the next is a constant so it is arithmetic sequence
first term: a = 10
difference: d = -4
so the formula:
8)
-3, -10, -17, -24, ...
-10-(-3) = -7; -17-(-10) = -7; -24-(-17) = -7
The difference between one term and the next is a constant so it is arithmetic sequence
first term: a = -3
difference: d = -7
so the formula:
9)
7, 8.5, 10, 11.5, ...
8.5-7 = 1.5; 10-8.5 = 1.5; 11.5-10 = 1.5
The difference between one term and the next is a constant so it is arithmetic sequence
first term: a = 7
difference: d = 1.5
so the formula:
10)
30, 22¹/₂, 15, 7¹/₂, ...
22¹/₂-30 = -7¹/₂; 15-22¹/₂ = -7¹/₂; 7¹/₂-15 = -7¹/₂
The difference between one term and the next is a constant so it is arithmetic sequence
first term: a = 30
difference: d = -7¹/₂
so the formula:
Answer:
89.29%
Step-by-step explanation:
Given that Scott answered exactly two questions wrong. He answered the last question wrong, the 26 questions before it correctly, and the question before that wrong. Since Amy and Scott were both incorrect on the same question exactly once, Scott would have done wrong only in I or II or III question. If I question was wrong by both, total questions = 28, if II wrong total questions =29 and for iii total questions =30
Greatest possible percent would occur if total questions are less
i.e. when total =28
Greatest percent =
Answer:
An Algebraic Expression that models the situation is
Step-by-step explanation:
Beginning balance of Jennifer=$4750
Now she deposits a paycheck = p
So, New balance = 4750+p
Now she writes a check = c
Remaining balance = 4750+p-c
Now she writes a check = d
Remaining balance = 4750+p-c-d
Now refunded some money (r) for returning a pair of shoes she bought.
New balance = 4750+p-c-d+r
Hence an Algebraic Expression that models the situation is
Answer:
Perimeter of square = 24 meter
Step-by-step explanation:
Given:
Square divided into three equal rectangle
Perimeter of rectangle = 16 meter
Find:
Perimeter of square
Computation:
We know that rectangle are equal
So,
3b = l
Perimeter of rectangle = 2 (l + b)
16 = 2 (l + b)
16 = 2 (3b + b)
b = 2 meter
l = 3 (2) = 6 meter
Side of square = 6 meter
Perimeter of square = 4(side)
Perimeter of square = 4(6)
Perimeter of square = 24 meter